Glass fiber reinforced bulk molding compound and preparation method thereof

By adding modified hexagonal boron nitride and hybrid hexagonal boron nitride to the epoxy resin and compounding it with glass fiber, the problem of low thermal conductivity of existing epoxy resin group molding materials is solved, and the thermal conductivity is achieved and significantly improve the mechanical properties to meet the application requirements of high thermal conductivity.

CN119463232AActive Publication Date: 2025-02-18HUIZHOU ZONGSHENG ELECTRONICS MATERIAL CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411422866.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing epoxy resin group molding materials have low thermal conductivity and are difficult to meet the application requirements of high thermal conductivity.

Method used

By adding modified hexagonal boron nitride and hybrid hexagonal boron nitride to the epoxy resin as thermal filler and compounding it with glass fibers, a thermal conductivity path and filler network are constructed to improve the thermal conductivity and mechanical properties of the material.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of the cluster molding material, can meet the application requirements of high thermal conductivity requirements, and maintains the traditional excellent properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081334370000121
    Figure BDA0005081334370000121
Patent Text Reader

Abstract

The invention discloses a glass fiber reinforced bulk molding compound and a preparation method thereof, and relates to the technical field of bulk molding compounds, the preparation method comprises the following steps: adding 4, 4 '-diaminodiphenyl sulfone and 2-methylimidazole into N, N-dimethylformamide, uniformly stirring, adding daidzein epoxy resin, and uniformly stirring to obtain an epoxy resin mixed solution; adding an epoxy resin mixed solution and an acrylate copolymer into the modified hexagonal boron nitride dispersion liquid, stirring at room temperature, dipping glass fibers into the solution, filtering and drying to obtain heat-conducting glass fibers; heating and reacting the epoxy resin mixed solution, cooling to room temperature, sequentially adding a reactive diluent, dicyandiamide, aluminum hydroxide, modified hexagonal boron nitride, hybrid hexagonal boron nitride and a release agent, stirring at a high speed, adding a thickening agent, and stirring at a low speed to obtain an epoxy resin glue solution; and adding heat-conducting glass fibers into the epoxy resin glue solution, and kneading to obtain the glass fiber reinforced bulk molding compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bulk molding compounds, in particular to a glass fiber reinforced bulk molding compound and a preparation method thereof. Background Art

[0002] Glass fiber reinforced bulk molding compound is a new type of composite material widely used in the fields of electronics, electrical, and automobiles. Its excellent mechanical properties, dimensional stability, and heat resistance make it an important part of the manufacturing of high-performance components. However, with the rapid development of electronic devices and electric vehicles, the thermal management of products has become increasingly prominent. In order to effectively dissipate heat, improving the thermal conductivity of molding compounds has become a key issue that needs to be solved.

[0003] At present, epoxy-based molding compounds have excellent performance, especially after being compounded with glass fiber (glass fiber), the mechanical strength and heat resistance of the material have been significantly improved. However, the inherent thermal conductivity of epoxy resin is low, which limits its application in fields with high thermal conductivity requirements. Therefore, in order to improve the thermal conductivity of molding compounds, thermal conductive fillers can be added to the material.

[0004] The selection of thermal conductive materials directly affects the thermal conductivity and overall performance of the final product. Common thermal conductive fillers include alumina (Al2O3), boron nitride (BN), carbon nanotubes (CNT) and graphene. These materials have high thermal conductivity and can significantly improve the thermal conductivity of composite materials without significantly affecting the mechanical properties and processability of the molding compound.

[0005] Combining thermally conductive fillers with epoxy resin and glass fiber can produce bulk molding compounds with better thermal conductivity. In the production process of such composite materials, it is necessary to consider the uniform dispersion of thermally conductive fillers, the interface compatibility with the matrix material, and the impact on the overall performance of the material. On the basis of ensuring the traditional excellent performance of molding compounds, through reasonable formula design and processing technology, the thermal conductivity of the product can be significantly improved to meet the application requirements in the field of high thermal conductivity requirements. Summary of the invention

[0006] The object of the present invention is to provide a glass fiber reinforced bulk molding compound and a preparation method thereof, so as to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A preparation method of a glass fiber reinforced bulk molding compound comprises the following steps: S1: adding hexagonal boron nitride, zirconium oxide, and urea aqueous solution into a ball mill, ball milling at room temperature for 16-20 hours, washing with deionized water, and vacuum drying at 60° C. for 12 hours to obtain small-sized hexagonal boron nitride;

[0009] Furthermore, the ball milling rate is 800-1000r / min;

[0010] S2: Add daidzein, tetrabutylammonium bromide and epichlorohydrin into a reaction vessel, heat to 100-105°C for reaction for 1.5-2h, cool to room temperature, add 50wt% sodium hydroxide solution, heat to 60-65°C for reaction for 5-5.5h, filter, dry overnight with magnesium sulfate, remove the solvent by rotary evaporation, and vacuum dry at 60°C for 12h to obtain daidzein epoxy resin;

[0011] Furthermore, in the soy aglycone epoxy resin, the molar ratio of soy aglycone:tetrabutylammonium bromide:epichlorohydrin is (0.1-0.2):(3.65-4.75):(1-2);

[0012] S3: ultrasonically dispersing hexagonal boron nitride in N,N-dimethylformamide, adding soybean aglycone, heating to 30-32°C and stirring for 6-6.5h, filtering, washing with ethanol, vacuum drying at 65°C for 12h, and continuing to heat to 200-205°C for 3.5-4h to obtain modified hexagonal boron nitride;

[0013] Furthermore, in the modified hexagonal boron nitride, the mass ratio of daidzein to hexagonal boron nitride is (0.4-0.5):1;

[0014] S4: ultrasonically disperse the small-sized hexagonal boron nitride in a sulfonyl chloride-chloroform mixed solution, stir at room temperature for 48 hours, ultrasonicate for 20-30 minutes every 6-8 hours, filter, wash with dichloromethane, and vacuum dry at 100°C for 12 hours to obtain activated hexagonal boron nitride;

[0015] Furthermore, in the sulfonyl chloride-chloroform mixed solution, the volume ratio of sulfonyl chloride to chloroform is 1:1;

[0016] S5: Under a nitrogen atmosphere, activated hexagonal boron nitride and furanyl chloride are added into a reaction vessel, heated to 60-65° C. for reaction for 6-6.5 h, washed with tetrahydrofuran, and dried under vacuum at 50° C. for 5 h to obtain furan hexagonal boron nitride;

[0017] Furthermore, in the furan hexagonal boron nitride, the mass ratio of activated hexagonal boron nitride to furancarbonyl chloride is 1:(0.8-1);

[0018] S6: ultrasonically disperse furan hexagonal boron nitride in tetrahydrofuran, add maleimide-polyethylene glycol, stir at room temperature for 48 hours, filter, wash with tetrahydrofuran, and vacuum dry at 25°C for 24 hours to obtain grafted hexagonal boron nitride;

[0019] Furthermore, in the grafted hexagonal boron nitride, the mass ratio of furan hexagonal boron nitride to maleimide-polyethylene glycol is 5:(3-4);

[0020] S7: Add silver acetate and 2-ethyl-4-methylimidazole to dichloromethane, stir evenly, add grafted hexagonal boron nitride, stir evenly, age at room temperature for 24 hours, and dry by rotary evaporation to remove the solvent to obtain hybrid hexagonal boron nitride;

[0021] Furthermore, in the hybrid hexagonal boron nitride, the molar ratio of silver acetate to 2-ethyl-4-methylimidazole is 2:1; the total mass of silver acetate and 2-ethyl-4-methylimidazole to the mass ratio of grafted hexagonal boron nitride is 1:(0.32-1.6);

[0022] S8: Add 4,4′-diaminodiphenyl sulfone and 2-methylimidazole to N,N-dimethylformamide, stir evenly, add soybean aglycone epoxy resin, stir evenly to obtain epoxy resin mixed solution; add epoxy resin mixed solution and acrylate copolymer to modified hexagonal boron nitride dispersion, stir at room temperature for 12-14 hours, immerse glass fiber in the solution, filter, and dry at 120°C for 3-5 hours to obtain thermal conductive glass fiber;

[0023] Furthermore, in the epoxy resin mixed solution, the mass ratio of soybean aglycone epoxy resin: 4,4′-diaminodiphenyl sulfone: 2-methylimidazole is (100-120): (3.4-4.2): (0.06-0.07); in the thermal conductive glass fiber, the mass ratio of epoxy resin mixed solution: acrylate copolymer: modified hexagonal boron nitride is (100-120): (8.4-13.6): (12.8-16.4);

[0024] Furthermore, the modified hexagonal boron nitride dispersion liquid solvent is N-methylpyrrolidone;

[0025] S9: Heat the epoxy resin mixed solution to 105-110°C and react for 25-30 minutes, cool to room temperature, add active diluent, dicyandiamide, curing accelerator, aluminum hydroxide, modified hexagonal boron nitride, hybrid hexagonal boron nitride, and release agent in sequence, stir at high speed for 15-20 minutes, add thickener, stir at low speed for 5-10 minutes, and obtain epoxy resin glue; add thermal conductive glass fiber to the epoxy resin glue, knead for 15-25 minutes, and obtain glass fiber reinforced bulk molding compound.

[0026] Further, the proportion of each component in the epoxy resin glue, by mass fraction, includes: 100-150 parts of epoxy resin mixed solution, 15-30 parts of active diluent, 10-15 parts of dicyandiamide, 3-5 parts of curing accelerator, 100-120 parts of aluminum hydroxide, 2.5-7.5 parts of modified hexagonal boron nitride, 13.5-17.5 parts of hybrid hexagonal boron nitride, 0.1-0.15 parts of release agent, and 6.8-7.2 parts of thickener; the proportion of each component in the glass fiber reinforced bulk molding compound, by mass fraction, includes: 100-120 parts of epoxy resin glue and 10-30 parts of thermal conductive glass fiber;

[0027] Further, the active diluent includes MF101 modified multifunctional active diluent;

[0028] Further, the release agent includes zinc stearate;

[0029] Further, the curing accelerator includes 2,4,6-tris(dimethylaminomethyl)phenol;

[0030] Further, the thickener includes polyether polyurethane;

[0031] Furthermore, the high-speed stirring rate is 1200-1500 r / min, and the low-speed stirring rate is 450-500 r / min.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention selects hexagonal boron nitride and urea aqueous solution as raw materials, and uses zirconium oxide as a ball milling medium to prepare small-sized amino-functionalized hexagonal boron nitride by ball milling; then, a large number of amino and hydroxyl active functional groups are generated at the edge of the small-sized hexagonal boron nitride by reacting with sulfonyl chloride, and then with furanyl chloride to introduce the furan group into the edge, and through the Diels-Alder addition reaction, the double-arm polyethylene glycol structure is introduced into the edge of the hexagonal boron nitride, which greatly improves its dispersibility and compatibility in epoxy resin and reduces the interface thermal resistance. It is compounded with hexagonal boron nitride (modified hexagonal boron nitride) in proportion as a composite thermal conductive filler and added to the epoxy resin, and the small-sized hexagonal boron nitride can fill the gaps between the hexagonal boron nitride (modified hexagonal boron nitride) to effectively construct a filler network and form a thermal conductive path, further improving the thermal conductivity and mechanical properties of the composite material. In order to further improve the ability of small-sized boron nitride to fill gaps and construct a thermal conductive network, silver acetate-imidazole complex is deposited on the surface of small-sized hexagonal boron nitride. Due to the introduction of polyethylene glycol structure, it exists at the edge of small-sized hexagonal boron nitride and does not affect the deposition of silver acetate-imidazole complex. Silver acetate-imidazole complex deposition can make use of the excellent dispersibility and compatibility of small-sized boron nitride to uniformly fill gaps and disperse in epoxy resin. During the heating and curing process, the silver acetate-imidazole complex deposition will decompose to produce 2-ethyl-4-methylimidazole, which promotes the curing of epoxy resin. At the same time, silver ions are reduced to nanosilver, which is melt-sintered to fill the gaps and connect with hexagonal boron nitride to form a longitudinal-lateral 3D thermal conductive path, further improving the cross-linking density and thermal conductivity of epoxy resin.

[0034] 2, the present invention uses soybean aglycone as raw material to make soybean aglycone epoxy resin respectively and carry out covalent modification to hexagonal boron nitride by large π bond, on the one hand, soybean aglycone epoxy resin is compared with traditional bisphenol A type epoxy resin, the cycloaddition reaction of the pyrone ring in its structure can further improve the cross-linking density of natural flavonoid epoxy resin, is conducive to the coordinated improvement of epoxy resin mechanical property and thermal stability, on the other hand, the aromatic benzene ring coupling structure in modified hexagonal boron nitride and soybean aglycone epoxy resin structure has π-π stacking effect, greatly improves the dispersibility and compatibility of modified hexagonal boron nitride in epoxy resin, improves the tightness connected with epoxy resin, further improves the thermal conductivity and mechanical property of matrix. In order to further improve thermal conductivity, the present invention impregnates glass fiber in the mixture of modified hexagonal boron nitride, acrylate copolymer and soybean aglycone epoxy resin, prepares heat-conducting glass fiber, and purpose is to build a planar heat-conducting layer, reduces the interface thermal resistance between glass fiber and epoxy resin matrix. The thermally conductive glass fiber is then compounded with an epoxy resin matrix (epoxy resin adhesive) to provide a planar thermal conductive path while avoiding excessive degradation of mechanical properties, thereby further improving the thermal conductivity and mechanical properties of the bulk molding compound. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In the following embodiments, hexagonal boron nitride specifications: lateral size: 2-4 μm, thickness: 200-300 nm, purchased from Dandong Rijin Technology Co., Ltd.; maleimide-polyethylene glycol model is 2-arm PEG-MAL, purchased from Sinobond; acrylate copolymer model is SG-708-6, specification: Mn=566946, purchased from Japan Nagase ChemteX Company; MF101 modified multifunctional active diluent, purchased from Hubei Zhenzhengfeng New Materials Co., Ltd.; polyether polyurethane, purchased from Guangdong Nanhui New Materials Co., Ltd.; glass fiber specifications: diameter 7 μm, length 9 mm, purchased from China Jushi; bisphenol A epoxy resin specifications: epoxy equivalent = 425 g / eq, purchased from Midland Dow Company, USA; the remaining raw materials are all commercially available.

[0037] In the following examples, a method for preparing small-sized hexagonal boron nitride comprises the following steps: adding 1 g of hexagonal boron nitride, 1 g of zirconium oxide, and a urea aqueous solution containing 160 g of urea into a ball mill, ball milling at room temperature for 20 h, washing with deionized water, and vacuum drying at 60° C. for 12 h to obtain small-sized hexagonal boron nitride;

[0038] The preparation method of soybean aglycone epoxy resin comprises the following steps: adding 0.0 mol of soybean aglycone, 3.65 mol of tetrabutylammonium bromide and 1 mol of epichlorohydrin into a reaction container, heating to 100° C. for reaction for 1.5 hours, cooling to room temperature, adding 40 g of 50 wt% sodium hydroxide solution, heating to 60° C. for reaction for 5 hours, filtering, drying with magnesium sulfate overnight, rotary evaporation to remove the solvent, and vacuum drying at 60° C. for 12 hours to obtain soybean aglycone epoxy resin;

[0039] The preparation method of modified hexagonal boron nitride comprises the following steps: ultrasonically dispersing 1 g of hexagonal boron nitride in N,N-dimethylformamide, adding 0.4 g of daidzein, heating to 30° C. and stirring for 6 h, filtering, washing with ethanol, vacuum drying at 65° C. for 12 h, and continuing to heat to 200° C. and heat treating for 3.5 h to obtain modified hexagonal boron nitride;

[0040] The preparation method of hybrid hexagonal boron nitride comprises the following steps: ultrasonically dispersing 10 small-sized hexagonal boron nitrides in 200 mL of a sulfonyl chloride-chloroform mixed solution, stirring at room temperature for 48 hours, ultrasonicating for 20 minutes every 6 hours, filtering, washing with dichloromethane, and vacuum drying at 100° C. for 12 hours to obtain activated hexagonal boron nitride; in a nitrogen atmosphere, adding 1 g of activated hexagonal boron nitride and 0.8 g of furanyl chloride into a reaction container, heating to 60° C. for reaction for 6 hours, washing with tetrahydrofuran, and vacuum drying at 50° C. for 5 hours to obtain furanyl chloride. Hexagonal boron nitride; ultrasonically disperse 5 g of furan hexagonal boron nitride in tetrahydrofuran, add 3 g of maleimide-polyethylene glycol, stir at room temperature for 48 hours, filter, wash with tetrahydrofuran, and vacuum dry at 25°C for 24 hours to obtain grafted hexagonal boron nitride; add 0.2 mol of silver acetate and 0.1 mol of 2-ethyl-4-methylimidazole to 100 mL of dichloromethane, stir evenly, add 14 g of grafted hexagonal boron nitride, stir evenly, age at room temperature for 24 hours, and rotary evaporate to remove the solvent to obtain hybrid hexagonal boron nitride.

[0041] Embodiment 1: A method for preparing a glass fiber reinforced bulk molding compound: S1: Add 3.4 parts of 4,4′-diaminodiphenyl sulfone and 0.06 parts of 2-methylimidazole to N,N-dimethylformamide, stir evenly, add 100 parts of soybean aglycone epoxy resin, stir evenly, and obtain an epoxy resin mixed solution; add 100 parts of the epoxy resin mixed solution and 8.4 parts of an acrylate copolymer to 12.8 parts of a modified hexagonal boron nitride dispersion, stir at room temperature, immerse the glass fiber in the solution, filter, and dry to obtain a thermally conductive glass fiber;

[0042] S2: Heat 100 parts of epoxy resin mixed solution to 105°C for reaction for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 2.5 parts of modified hexagonal boron nitride, 17.5 parts of hybrid hexagonal boron nitride, 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin glue; add 10 parts of thermal conductive glass fiber to 100 parts of epoxy resin glue, knead, and obtain glass fiber reinforced bulk molding compound.

[0043] Example 2: A method for preparing a glass fiber reinforced bulk molding compound: S1: Add 3.4 parts of 4,4′-diaminodiphenyl sulfone and 0.06 parts of 2-methylimidazole to N,N-dimethylformamide, stir evenly, add 100 parts of soybean aglycone epoxy resin, stir evenly, and obtain an epoxy resin mixed solution; add 100 parts of the epoxy resin mixed solution and 8.4 parts of an acrylate copolymer to 16.4 parts of a modified hexagonal boron nitride dispersion, stir at room temperature, immerse the glass fiber in the solution, filter, and dry to obtain a thermally conductive glass fiber;

[0044] S2: Heat 100 parts of epoxy resin mixed solution to 105°C for reaction for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 2.5 parts of modified hexagonal boron nitride, 17.5 parts of hybrid hexagonal boron nitride, 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin glue; add 10 parts of thermal conductive glass fiber to 100 parts of epoxy resin glue, knead, and obtain glass fiber reinforced bulk molding compound.

[0045] Example 3: A method for preparing a glass fiber reinforced bulk molding compound: S1: Add 3.4 parts of 4,4′-diaminodiphenyl sulfone and 0.06 parts of 2-methylimidazole to N,N-dimethylformamide, stir evenly, add 100 parts of soybean aglycone epoxy resin, stir evenly, and obtain an epoxy resin mixed solution; add 100 parts of the epoxy resin mixed solution and 8.4 parts of an acrylate copolymer to 16.4 parts of a modified hexagonal boron nitride dispersion, stir at room temperature, immerse the glass fiber in the solution, filter, and dry to obtain a thermally conductive glass fiber;

[0046] S2: Heat 100 parts of epoxy resin mixed solution to 105°C for reaction for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 7.5 parts of modified hexagonal boron nitride, 12.5 parts of hybrid hexagonal boron nitride, 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin glue; add 10 parts of thermal conductive glass fiber to 100 parts of epoxy resin glue, knead, and obtain glass fiber reinforced bulk molding compound.

[0047] Example 4: A method for preparing a glass fiber reinforced bulk molding compound: S1: Add 3.4 parts of 4,4′-diaminodiphenyl sulfone and 0.06 parts of 2-methylimidazole to N,N-dimethylformamide, stir evenly, add 100 parts of soybean aglycone epoxy resin, stir evenly, and obtain an epoxy resin mixed solution; add 100 parts of the epoxy resin mixed solution and 8.4 parts of an acrylate copolymer to 16.4 parts of a modified hexagonal boron nitride dispersion, stir at room temperature, immerse the glass fiber in the solution, filter, and dry to obtain a thermally conductive glass fiber;

[0048] S2: Heat 100 parts of epoxy resin mixed solution to 105°C for reaction for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 7.5 parts of modified hexagonal boron nitride, 12.5 parts of hybrid hexagonal boron nitride, 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin glue; add 30 parts of thermal conductive glass fiber to 100 parts of epoxy resin glue, knead, and obtain glass fiber reinforced bulk molding compound.

[0049] Comparative Example 1: A method for preparing a glass fiber reinforced bulk molding compound: heat 100 parts of an epoxy resin mixed solution to 105°C and react for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 2.5 parts of modified hexagonal boron nitride, 17.5 parts of hybrid hexagonal boron nitride, and 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes, and obtain epoxy resin adhesive; add 10 parts of glass fiber to 100 parts of epoxy resin adhesive, knead, and obtain a glass fiber reinforced bulk molding compound.

[0050] Comparative Example 2: A method for preparing a glass fiber reinforced bulk molding compound: heat 100 parts of an epoxy resin mixed solution to 105°C and react for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 20 parts of modified hexagonal boron nitride, and 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin adhesive; add 10 parts of thermal conductive glass fiber to 100 parts of epoxy resin adhesive, knead, and obtain a glass fiber reinforced bulk molding compound.

[0051] The remaining steps are the same as those in Example 1.

[0052] Comparative Example 3: A method for preparing a glass fiber reinforced bulk molding compound: heat 100 parts of an epoxy resin mixed solution to 105°C and react for 25 minutes, cool to room temperature, add 15 parts of MF101 modified multifunctional active diluent, 10 parts of dicyandiamide, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 100 parts of aluminum hydroxide, 20 parts of hybrid hexagonal boron nitride, and 0.1 part of zinc stearate in sequence, stir at high speed for 15 minutes, add 6.8 parts of polyether polyurethane, stir at low speed for 5 minutes to obtain epoxy resin adhesive; add 10 parts of thermal conductive glass fiber to 100 parts of epoxy resin adhesive, knead, and obtain a glass fiber reinforced bulk molding compound.

[0053] The remaining steps are the same as those in Example 1.

[0054] Comparative Example 4: A method for preparing a glass fiber reinforced bulk molding compound: A method for preparing a hybrid hexagonal boron nitride, comprising the following steps: ultrasonically dispersing 10 hexagonal boron nitride in 200 mL of a sulfonyl chloride-chloroform mixed solution, stirring at room temperature for 48 h, ultrasonicating for 20 min every 6 h, filtering, washing with dichloromethane, and vacuum drying at 100 ° C for 12 h to obtain activated hexagonal boron nitride; in a nitrogen atmosphere, adding 1 g of activated hexagonal boron nitride and 0.8 g of furanyl chloride to a reaction container, heating to 60 ° C for 6 h, washing with tetrahydrofuran, and vacuum drying at 50 ° C for 12 h. Air drying for 5 hours to obtain furan hexagonal boron nitride; ultrasonically disperse 5g of furan hexagonal boron nitride in tetrahydrofuran, add 3g of maleimide-polyethylene glycol, stir at room temperature for 48 hours, filter, wash with tetrahydrofuran, and vacuum dry at 25°C for 24 hours to obtain grafted hexagonal boron nitride; add 0.2mol of silver acetate and 0.1mol of 2-ethyl-4-methylimidazole to 100mL of dichloromethane, stir evenly, add 14g of grafted hexagonal boron nitride, stir evenly, age at room temperature for 24 hours, and rotary evaporate to remove the solvent to obtain hybrid hexagonal boron nitride.

[0055] The remaining steps are the same as those in Example 1.

[0056] Comparative Example 5: A method for preparing a glass fiber reinforced bulk molding compound: S1: Add 3.4 parts of 4,4′-diaminodiphenyl sulfone and 0.06 parts of 2-methylimidazole to N,N-dimethylformamide, stir evenly, add 100 parts of bisphenol A epoxy resin, stir evenly to obtain an epoxy resin mixed solution; add 100 parts of the epoxy resin mixed solution and 8.4 parts of acrylate copolymer to 12.8 parts of modified hexagonal boron nitride dispersion, stir at room temperature, immerse the glass fiber in the solution, filter, and dry to obtain thermal conductive glass fiber.

[0057] The remaining steps are the same as those in Example 1.

[0058] Comparative Example 6: A method for preparing a glass fiber reinforced bulk molding compound: A method for preparing hybrid hexagonal boron nitride, comprising the following steps: ultrasonically dispersing 10 small-sized hexagonal boron nitride in 200 mL of a sulfonyl chloride-chloroform mixed solution, stirring at room temperature for 48 hours, ultrasonicating for 20 minutes every 6 hours, filtering, washing with dichloromethane, and vacuum drying at 100°C for 12 hours to obtain activated hexagonal boron nitride; adding 0.2 mol of silver acetate and 0.1 mol of 2-ethyl-4-methylimidazole to 100 mL of dichloromethane, stirring evenly, adding 14 g of grafted hexagonal boron nitride, stirring evenly, aging at room temperature for 24 hours, and rotary drying to remove the solvent to obtain hybrid hexagonal boron nitride.

[0059] The remaining steps are the same as those in Example 1.

[0060] Experiment: The glass fiber reinforced bulk molding compound prepared in the above embodiments and comparative examples was preheated to 60°C, the bulk molding compound was weighed according to the mold volume, put into the mold, and then placed in a flat vulcanizer, pressurized to 8 MPa, and cured by step-heating at 80°C / 2h, 120°C / 1h, 150°C / 1h, and 160°C / 1h, and cooled to obtain the sample to be tested.

[0061] Thermal conductivity test: The thermal conductivity of the sample is tested at room temperature using the hot wire method of a thermal conductivity meter;

[0062] Mechanical properties test: Tested according to GB / T 2567-2005;

[0063] Volume resistivity test: Tested in accordance with GB / T 1409-2006.

[0064] The experimental data are shown in Table 1 below.

[0065] Table 1 Performance test data of glass fiber reinforced bulk molding compound

[0066]

[0067] Conclusion: The bulk molding compounds prepared in Examples 1-4 have excellent thermal conductivity and mechanical properties.

[0068] Since Comparative Example 1 uses ordinary commercially available glass fiber to replace the thermal conductive glass fiber; Comparative Example 2 uses entirely modified hexagonal boron nitride; Comparative Example 3 uses entirely hybrid hexagonal boron nitride; Comparative Example 4 uses ordinary hexagonal boron nitride to prepare hybrid hexagonal boron nitride; Comparative Example 5 uses ordinary bisphenol A epoxy resin in the process of preparing the thermal conductive glass fiber; and Comparative Example 6 uses polyvinyl alcohol to graft the edge of the boron nitride during the preparation of the hybrid hexagonal boron nitride, the performance of the prepared bulk molding compound is reduced.

[0069] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a glass fiber reinforced bulk molding compound, characterized in that: The following steps are involved: S1: Add 4,4′-diaminodiphenyl sulfone and 2-methylimidazole to N,N-dimethylformamide, stir evenly, add soybean aglycone epoxy resin, stir evenly to obtain epoxy resin mixed solution; add epoxy resin mixed solution and acrylate copolymer to modified hexagonal boron nitride dispersion, stir at room temperature, immerse glass fiber in the solution, filter, and dry to obtain thermal conductive glass fiber; S2: Heat the epoxy resin mixed solution to 105-110°C and react for 25-30 minutes, cool to room temperature, add active diluent, dicyandiamide, curing accelerator, aluminum hydroxide, modified hexagonal boron nitride, hybrid hexagonal boron nitride, and release agent in sequence, stir at high speed, add thickener, stir at low speed to obtain epoxy resin glue; add thermal conductive glass fiber to the epoxy resin glue, knead, and obtain glass fiber reinforced bulk molding compound.

2. The method for preparing a glass fiber reinforced bulk molding compound according to claim 1, characterized in that: In the epoxy resin mixed solution, the mass ratio of soybean aglycone epoxy resin: 4,4′-diaminodiphenyl sulfone: 2-methylimidazole is (100-120): (3.4-4.2): (0.06-0.07); in the thermal conductive glass fiber, the mass ratio of epoxy resin mixed solution: acrylate copolymer: modified hexagonal boron nitride is (100-120): (8.4-13.6): (12.8-16.4).

3. The method for preparing a glass fiber reinforced bulk molding compound according to claim 1, characterized in that: The proportions of the various components in the epoxy resin adhesive, calculated by mass fraction, include: 100-150 parts of epoxy resin mixed solution, 15-30 parts of active diluent, 10-15 parts of dicyandiamide, 3-5 parts of curing accelerator, 100-120 parts of aluminum hydroxide, 2.5-7.5 parts of modified hexagonal boron nitride, 13.5-17.5 parts of hybrid hexagonal boron nitride, 0.1-0.15 parts of release agent, and 6.8-7.2 parts of thickener; the proportions of the various components in the glass fiber reinforced bulk molding compound, calculated by mass fraction, include: 100-120 parts of epoxy resin adhesive and 20-50 parts of thermal conductive glass fiber.

4. The method for preparing a glass fiber reinforced bulk molding compound according to claim 1, characterized in that: The preparation method of the hybrid hexagonal boron nitride comprises the following steps: adding silver acetate and 2-ethyl-4-methylimidazole to dichloromethane, stirring evenly, adding grafted hexagonal boron nitride, stirring evenly, aging at room temperature, and drying by rotary evaporation to remove the solvent, thereby obtaining hybrid hexagonal boron nitride; In the hybrid hexagonal boron nitride, the molar ratio of silver acetate to 2-ethyl-4-methylimidazole is 2:1; the mass ratio of the total mass of silver acetate and 2-ethyl-4-methylimidazole to the grafted hexagonal boron nitride is 1:(0.32-1.6).

5. The method for preparing a glass fiber reinforced bulk molding compound according to claim 4, characterized in that: The preparation method of grafted hexagonal boron nitride comprises the following steps: ultrasonically dispersing furan hexagonal boron nitride in tetrahydrofuran, adding maleimide-polyethylene glycol, stirring at room temperature, filtering, washing with tetrahydrofuran, and vacuum drying to obtain grafted hexagonal boron nitride; In the grafted hexagonal boron nitride, the mass ratio of furan hexagonal boron nitride to maleimide-polyethylene glycol is 5:(3-4).

6. The method for preparing a glass fiber reinforced bulk molding compound according to claim 5, characterized in that: The preparation method of furan hexagonal boron nitride comprises the following steps: in a nitrogen atmosphere, adding activated hexagonal boron nitride and furanyl chloride into a reaction container, heating to 60-65° C. for reaction for 6-6.5 hours, washing with tetrahydrofuran, and vacuum drying to obtain furan hexagonal boron nitride; In the furan hexagonal boron nitride, the mass ratio of activated hexagonal boron nitride to furancarbonyl chloride is 1:(0.8-1).

7. The method for preparing a glass fiber reinforced bulk molding compound according to claim 6, characterized in that: The preparation method of activated hexagonal boron nitride comprises the following steps: ultrasonically dispersing small-sized hexagonal boron nitride in a sulfonyl chloride-chloroform mixed solution, stirring at room temperature for 48 hours, ultrasonically performing 20-30 minutes every 6-8 hours, filtering, washing with dichloromethane, and vacuum drying at 100° C. for 12 hours to obtain activated hexagonal boron nitride; In the sulfonyl chloride-chloroform mixed solution, the volume ratio of sulfonyl chloride to chloroform is 1:

1.

8. The method for preparing a glass fiber reinforced bulk molding compound according to claim 1, characterized in that: The preparation method of modified hexagonal boron nitride comprises the following steps: ultrasonically dispersing hexagonal boron nitride in N,N-dimethylformamide, adding daidzein, heating to 30-32°C and stirring for 6-6.5h, filtering, washing with ethanol, vacuum drying, and continuing to heat to 200-205°C for heat treatment for 3.5-4h to obtain modified hexagonal boron nitride; In the modified hexagonal boron nitride, the mass ratio of daidzein to hexagonal boron nitride is (0.4-0.5):

1.

9. The method for preparing a glass fiber reinforced bulk molding compound according to claim 1, characterized in that: The preparation method of the daidzein epoxy resin comprises the following steps: adding daidzein, tetrabutylammonium bromide and epichlorohydrin into a reaction container, heating to 100-105° C. for reaction for 1.5-2 hours, cooling to room temperature, adding 50wt% sodium hydroxide solution, heating to 60-65° C. for reaction for 5-5.5 hours, filtering, drying overnight with magnesium sulfate, rotary evaporation to remove the solvent, and vacuum drying to obtain the daidzein epoxy resin; In the soyglycoside epoxy resin, the molar ratio of soyglycoside:tetrabutylammonium bromide:epichlorohydrin is (0.1-0.2):(3.65-4.75):(1-2).

10. Glass fiber reinforced bulk molding compound prepared according to the method for preparing a glass fiber reinforced bulk molding compound according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Daidzein-based epoxy resin material and preparation method thereof

    CN116948147A

  • Preparation method of epoxy pouring sealant for chip packaging

    CN118496789A

  • Composite aluminum nitride powder and method for producing the same

    JP2021134121A

  • Method for producing maleimide polyethylene glycol derivative

    US20240043613A1